THE INFLUENCE OF DIABETES MELLITUS ON THE COURSE OF PURULENT THORACIC SURGICAL PATHOLOGIES (World Bulletin of Public Health, 2022)
A retrospective analysis of the clinical course of purulent thoracic surgical patients with diabetes mellitus (DM) and an assessment of the results of surgical treatment and their complications were performed. In 105 (30.1%) of 348 patients treated in the clinical base of BSMI, diabetes was diagnosed. As a result of the study, in patients with purulent thoracic surgical diseases against the background of diabetes, a complex peculiar clinical course is observed that is different from patients who do not have diabetes and leading to serious complications. Timely correction of hyperglycemia before and after surgery reduces the complications of diabetes mellitus, improves the effectiveness of surgical operations with purulent thoracic surgical diseases and leads to better treatment results. Such patients must be treated in conjunction with an endocrinologist.
Keywords: Purulent thoracic surgical diseases; diabetes mellitus; clinical course; treatment